Fintech and Financial Services : Initial Considerations - He, Dong.; Haksar, Vikram; Leckow, Ross.; Mancini Griffoli, Tommaso (Washington, D.C. : International Monetary Fund, 2017)
A new wave of technological innovations, often called 'fintech,' is accelerating change in the financial sector. What impact might fintech have on financial services, and how should regulation respond? This paper sets out an economic framework for thinking through the channels by which fintech might provide solutions that respond to consumer needs for trust, security, privacy, and better services, change the competitive landscape, and affect regulation. It combines a broad discussion of trends across financial services with a focus on cross-border payments and especially the impact of distributed ledger technology. Overall, the paper finds that boundaries among different types of service providers are blurring; barriers to entry are changing; and improvements in cross-border payments are likely. It argues that regulatory authorities need to balance carefully efficiency and stability trade-offs in the face of rapid changes, and ensure that trust is maintained in an evolving financial system. It also highlights the importance of international cooperation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet